Personalized training as a promoter for physical activity in people with depressive disorder—a randomized controlled trial in Germany - Keller-Varady, Katriona; Haufe, Sven; Schieffer, Elisabeth; Kerling, Arno; Tegtbur, Uwe; Kahl, Kai G. (Frontiers in Psychiatry, 2023)
Introduction: Adopting an active lifestyle is an important goal, but can be difficult to achieve for people with depressive disorders. Current guidelines recommend the integration of physical activity in the multimodal treatment of depressive disorders. However, the possibilities to provide individual support for physical activities are frequently limited. The aim of our study was to examine how physical activity can be increased in a real-world setting by combining physical training and psychological interventions. Materials and methods: In this randomized-controlled interventional study, 31 outpatients diagnosed with moderate to severe depression were recruited from the region of Hannover. The intervention group (n=16) was offered six weekly individual sessions lasting between 60 to 90 minutes with a sports scientist, including Motivational Interviewing and accompanied exercise activities. The control group (n=15) received a written booklet with information on steps towards becoming more active. Moderate-to-vigorous physical activity (MVPA) as the primary outcome was analyzed using activity sensors before and after the 6-week intervention, and three months subsequently. Secondary outcomes included the Six-Minute Walk Test (6MWT), Sit-to-Stand test (STS), and mental health assessed with self-rating questionnaires. Results: In the intervention group, MVPA increased significantly between baseline and the first follow-up and remained at an increased level at the second follow-up in comparison to decreased levels in the control group (difference of 15.5 min/day between groups over time, SE = 6.2 min/day, 95%-CI[2.7, 28.3], p=0.020). The increased activity level was associated with markers of increased fitness (6MWT and STS) in the intervention group. Both groups showed comparable improvements in depressive symptoms, while the number of patients receiving antidepressants increased in the control group and decreased in the intervention group. Two patients dropped out of the intervention group during the trial. Conclusion: The intervention proved to be a feasible and effective aid to promote a physically active lifestyle for patients diagnosed with depression. Furthermore, the higher level of physical activity was maintained for the follow-up period. Given the success of the approach evaluated in this project, individual support for physical activity should be investigated in larger sample sizes and potentially be considered in the multimodal treatment of depression.